Perlindungan Hak Kekayaan Intelektual (HKI) bagi Usaha Kreatif Lokal dalam Mendukung Sektor Pariwisata - Seharja, Sesde; Rusmini, Andin (PT. PENERBIT TIGA MUTIARA, 2023)
Tourism and the creative industry have an inseparable link, these two things are an emotional link between visitors and the tourist destinations they visit, namely in the form of souvenirs, as mementos to take home after traveling. Advances in digital technology have increased the distribution of information related to work and creativity so that the risk of work theft and copyright infringement is very vulnerable to occurring and this can be detrimental to creative industry players. This research uses qualitative methods with a literature approach in the form of laws, government regulations, articles and books that are relevant to the research topic. This research aims to provide an understanding of the importance of registering Intellectual Property Rights for creative industry to ensure the law protection of the intellectual property that has been created. The research results show that every creative industry player needs to register copyrighted works with the Directorate General of Intellectual Property. Apart from that, synergy is needed between the Government and the public in increasing awareness of creators or creative industry players to register copyrighted works as Intellectual Property Rights through regulations and facilities provided by the authorized government institution, namely the Directorate General of Intellectual Property, Ministry of Law and Rights. Indonesian Human Rights so that creative works receive legal protection.